Sex Disparities in Productivity among Oculoplastic Surgeons - Chiam, Mckenzee; Camacci, Mona L.; Khan, Alicia; Lehman, Erik B.; Pantanelli, Seth M. (Journal of Academic Ophthalmology, 2021)
Purpose The aim of the study is to investigate sex differences in academic rank, publication productivity, and National Institute of Health (NIH) funding among oculoplastic surgeons and whether there is an association between American Society of Ophthalmic Plastic and Reconstructive Surgery (ASOPRS) membership and scholarly output.Methods Sex, residency graduation year, and academic rank were obtained from institutional websites of 113 U.S. ophthalmology programs. H-indices and m-quotients were obtained from the Scopus database. NIH funding information was obtained from the NIH Research Portfolio Online Reporting Tool.Results Of the 272 surgeons, 74 (30.2%) were females. When adjusted for career duration, differences in female to male proportions were only significant at the rank of assistant professor (assistant: 74.3 vs. 48.5%, p = 0.047; associate: 18.9 vs. 24.6%, p = 0.243; full professor: 13.0 vs. 37.2%, p = 0.114). Women had a shorter career duration than men [10.0 (interquartile range or IQR 12.0) vs. 21.0 (IQR 20.0) years; p < 0.001] and a lower h-index [4.0 (IQR 5.0) vs. 7.0 (IQR 10.0); p < 0.001], but similar m-quotients [0.4 (IQR 0.4) vs. 0.4 (IQR 0.4); p = 0.9890]. Among ASOPRS members, females had a lower h-index than males [5.0 (IQR 6.0) vs. 9.0 (IQR 10.0); p < 0.001] due to career length differences. No difference in productivity between sexes was found among non-ASOPRS members. ASOPRS members from both sexes had higher scholarly output than their non-ASOPRS counterparts. Just 2.7% (2/74) of females compared with 5.3% (9/171) of males received NIH funding (p = 0.681).Conclusion Sex differences in academic ranks and h-indices are likely due to the smaller proportion of females with long career durations. ASOPRS membership may confer opportunities for increased scholarly output.
Keywords: oculoplastic; ophthalmology; academic rank; publication productivity; NIH funding; disparities; gender